PENGARUH PERTUMBUHAN EKONOMI, SUKU BUNGA, DAN NILAI TUKAR TERHADAP INVESTASI ASING LANGSUNG DI INDONESIA - Sari, Gusti Agung Ayu Ratih Meita; Baskara, I Gde Kajeng (E-Jurnal Manajemen, 2018)
Foreign direct investment is one of the alternative sources for funding to assist development in Indonesia. Economic growth, interest rate, and exchange rate are considered to have an effect on the size of foreign direct investment in a country. This study aimed to determine the effect of economic growth, interest rate, and exchange rate to foreign direct investment in Indonesia. The research data source is secondary data from the  the foreign direct investment, economic growth, interest rate, and exchange rate during the quarter of 2004 until second quarter of 2017. This study uses multiple linear regression analysis technique. This study found that economic growth has a positive but insignificant effect on foreign direct investment, interest rate has a significant negative effect and exchange rates has a positive significant on foreign direct investment in Indonesia.